The diagnostic accuracy of three rapid diagnostic tests for typhoid fever at Chittagong Medical College Hospital, Chittagong, Bangladesh. Issue 10 (15th July 2015) - Maude, Rapeephan R.; de Jong, Hanna K.; Wijedoru, Lalith; Fukushima, Masako; Ghose, Aniruddha; Samad, Rasheda; Hossain, Mohammed Amir; Karim, Mohammed Rezaul; Faiz, Mohammed Abul; Parry, Christopher M.; CMCH Typhoid Study Group; Sayeed, Abdullah Abu; et al.
Abstract Objective To determine the diagnostic accuracy of three rapid diagnostic tests (RDTs) for typhoid fever in febrile hospitalised patients in Bangladesh. Methods Febrile adults and children admitted to Chittagong Medical College Hospital, Bangladesh, were investigated with Bact/Alert® blood cultures and real‐time PCR to detect Salmonella enterica Typhi and Paratyphi A and assays for Rickettsia, leptospirosis and dengue fever. Acute serum samples were examined with the LifeAssay (LA) Test‐it™ Typhoid IgM lateral flow assay detecting IgM antibodies against S. Typhi O antigen, CTKBiotech Onsite Typhoid IgG/IgM Combo Rapid‐test cassette lateral flow assay detecting IgG and IgM antibodies against S. Typhi O and H antigens and SD Bioline line assay for IgG and IgM antibodies against S. Typhi proteins. Results In 300 malaria smear‐negative febrile patients [median (IQR) age of 13.5 (5–31) years], 34 (11.3%) had confirmed typhoid fever: 19 positive by blood culture for S. Typhi (three blood PCR positive) and 15 blood culture negative but PCR positive for S. Typhi in blood. The respective sensitivity and specificity of the three RDTs in patients using a composite reference standard of blood culture and/or PCR‐confirmed typhoid fever were 59% and 61% for LifeAssay, 59% and 74% for the CTK IgM and/or IgG, and 24% and 96% for the SD Bioline RDT IgM and/or IgG. The LifeAssay RDT had a sensitivity of 63% and a specificity of 91% when modified with a positive cut‐off of ≥2+ and analysed using a Bayesian latent class model. Conclusions These typhoid RDTs demonstrated moderate diagnostic accuracies, and better tests are needed.